Effect of different methods of deacidification on the properties of noni (Morinda citrifolia) extract - Yap, Yenny; Muhammad Afwan Jamil,; Haslaniza Hashim,; Mohamad Yusof Maskat, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Deacidification of fruit extracts is necessary in certain situations which include consumer preference and product application. Although deacidification of noni extract using ion exchange resin and calcium carbonate addition has been reported, comparison between the two methods is lacking. This study was conducted to compare the effects of different deacidification treatments of ion exchange resin and calcium carbonate on the properties of noni extract. Ion exchange resin (Amberlite IRA-67) (R), calcium carbonate addition (CC), ion exchange resin followed by calcium carbonate addition (RC) and calcium carbonate addition followed by ion exchange resin (CR) were used to deacidify noni extract. Subsequently, analysis for pH, total soluble solids (TSS), total phenolic content (TPC), free radical scavenging ability (DPPH) and ferric reducing power (FRAP) were carried out. Compared to control, TPC, DPPH, and FRAP of noni extract decreased significantly (p<0.05) after deacidification using all different treatments. pH increased significantly (p<0.05) for all samples. TSS decreased significantly (p<0.05) after deacidification using all different treatments except for samples using resin (R) and calcium carbonate (CC). Deacidification using resin (R) produced a higher pH but lower TPC, DPPH and FRAP compared to calcium carbonate (CC). Ion exchange resin followed by calcium carbonate (RC) produced a lower (p<0.05) DPPH compared to calcium carbonate followed by ion exchange resin (CR). Deacidification of noni extract using calcium carbonate (CC) was the best method as it produced the smallest (p<0.05) reduction per change of pH for FRAP and no significant difference for DPPH compared to ion exchange resin (R).